A Novel Approach of Controlling Stoppage of Drip Infusion Using Image Processing on Raspberry PI Platform: A Novel Approach of Controlling Stoppage of Drip Infusion - Pranjoto, Hartono; Agustine, Lanny; Lestariningsih, Diana; Werdani, Yesiana Dwi Wahyu; Andyardja, Widya; Filipe, Jose Maria Leao; Atoum, Manar Fayiz Mousa; Yaro, Abubakar (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Intravenous drip diffusion is a common practice to treat patients in hospitals. During treatment, nurses must check the condition of the infusion bag frequently before running out of fluid. This research proposes a novel method of checking the infusion bag using an image processing technique on a compact Raspberry PI platform. The infusion monitoring system proposed here is based solely on capturing the image of the infusion bag and the accompanying bag/ tube. When the infusion fluid enters the patient, the surface of the liquid will decrease, and at the end will reach the bottom of the infusion bag. When the image of the fluid surface touches the bottom of the infusion bag, a mechanism will trigger a relay, and then activate a pinch valve to stop the flow of the infusion fluid before it runs out. The entire system incorporates a digital camera and Raspberry as the image processor. The surface of the liquid is determined using the Canny Edge Detection algorithm, and its relative position in the tube is determined using the Hough Line Transform. The raw picture of the infusion bag and the processed image are then sent via a wireless network to become part of a larger system and can be monitored via a simple smartphone equipped with the proper application, thus becoming an Internet of Things (IoT). With this approach, nurses can carry on other tasks in caring for the patients while this system substitutes some work on checking the infusion fluid.